(untitled) (Revista "Boletín el Conuco", 2022)
Objective: to determine, based on gender differences, the perceptions that consumers have regarding the social responsibility practices of some banks operating in Colombia. Method: A quantitative study was developed to analyze a convenience sample of 588 account holders. Results: In general terms, both genders agree that banks should maintain a strong competitive position, if they contribute to the economic growth of the country. Discussion: The scientific and business literature reveals a growing interest in delving into the impact of corporate social responsibility. The general conceptualization refers that companies should comply not only with economic objectives but also with legal, environmental, ethical, and philanthropic ones. Conclusions: It is concluded that men perceive the ethical behavior of the bank in a better way and that women give a more favorable perception to the compliance of legal aspects by the financial entity.